ASSESSMENT OF COGNITIVE ABILITIES OF ADOLESCENTS - Топчій, Марія; Босенко, Анатолій (SWorldJournal, 2024)
To study the impact of physical exertion on the psycho-emotional state of adolescents aged 11–14 years who are engaged in karate sections. There were examined 14 adolescents aged 11–14 years, who have been engaged in Koshiki Karate-Do for three years. The